2022
DOI: 10.52711/0974-360x.2022.00197
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative account on Antioxidant activities, Total phenolic and Flavonoid contents of Punica granatum, Carica papaya, Foeniculum vulgare, Trigonella foenum-graecum, and Urtica dioica: An in vitro Evaluation

Abstract: Antioxidant potential of aqueous extracts was determined individually and ABTS/DPPH free radicals were utilized for scoring antioxidant activities, Folin-Ciocalteau’s reagent for Total Phenolic content and aluminum chloride colorimetry method for Total Flavonoid content evaluation. Different parts of the same plant exhibited different antioxidant potential. An overall comparative account among the different parts of selected fruits, spices and herb can be stated as Punica granatum (PG) peel˃ Punica granatum pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…At present, the consumption of synthetic supplements, such as N-acetyl cysteine (NAC), as antioxidants has been shown to promote negative health effects [ 5 ]. As alternatives to synthetic compounds, antioxidants derived from natural extracts from plants possess bioactive qualities that bring additional value to the final products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the consumption of synthetic supplements, such as N-acetyl cysteine (NAC), as antioxidants has been shown to promote negative health effects [ 5 ]. As alternatives to synthetic compounds, antioxidants derived from natural extracts from plants possess bioactive qualities that bring additional value to the final products.…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of promising plant-based raw materials, as well as the assessment of their chemical components and pharmacological activities, is especially crucial when designing new medicines for both disease prevention and treatment. As a result, it is critical to use the latest scientific techniques to evaluate the chemical composition of herbal extracts used in traditional and folk medicine to identify which raw materials have the highest anticancer, antioxidant and other ethnopharmacological activities in vitro and in vivo [ 5 ]. Antioxidant compounds include nonenzymatic polyphenols consumed through diet and antioxidant enzymes physiologically generated by the body.…”
Section: Introductionmentioning
confidence: 99%
“…The other researchers have also declared a positive and significant association between antioxidant activity and the plant total phenol and total flavonoid conten 54 , 58 , 59 . Himalian and Singh 60 reported that flavonoids increase the antioxidant activity of the plant.…”
Section: Resultsmentioning
confidence: 99%
“…Plants have an orchestra of phytochemical elements, such as polyphenols (flavonoids, phenolic acids), alkaloids, terpenoids minerals, and tannins, which act as secondary metabolites hence, have a critical role the strengthening therapeutic qualities against different ailments. There is a role for polyphenols as direct antioxidants that scavenge ROS, and these ethnobotanicals are in good sync with nature, with no side effects [ 27 ]. Achieving a balance between ROS and natural antioxidants is significant and could be a key mechanism for reducing damage related to oxidative stress induced by harmful substances.…”
Section: Plant-based Nanomedicinementioning
confidence: 99%